Expressive Speech Acts of Complaining in The Anime “Tanaka Kun Wa Itsumo Kedaruge” (Pragmatics Study) - Uning Kuraesin; Muhamad Ilham Prasetya (IZUMI, 2022)
Language is used to communicate with fellow human beings on this earth, with language we can understand what other people want to convey to us either in spoken, written, formal or informal language. With the language we perform an action to convey the language to the speech partner or often referred to as our interlocutor in order to capture the meaning of what we convey or we say. In language there are speech acts, speech acts are part of pragmatics. A speech act is an utterance of a sentence to state that a purpose of the speaker is known by the interlocutor. In the speech act itself there are three main parts, called locution, illocution and perlocution. Each of the three main pillars has its own function in performing a speech so that a speech can be easily understood by the interlocutor. This study aims to describe the forms of speech acts and complaining strategies used in a Japanese animation This study uses qualitative descriptive method by examining the utterances that occur in the data. The Data used by the researchers were obtained from the anime entitled Tanaka kun wa Itsumo Kedaruge where in the anime there are many complaints that become the source of research. Data analysis is done by classifying the form of speech acts and complaining strategies used using existing theories. The results of the study found that the form of speech acts was 51 data with the form of direct speech acts as many as 22 data, the form of indirect speech acts as many as 29 data. From the results of the discussion, Complaint data found 51 data with implicit complaints with 17 data cues sub- category (hint), expressions of annoyance/disapproval with 31 data sub-categories annoyance, 2 data of painful consequences sub-category (ill consequences), accusations with category of direct accusation (direct accusation) as much as 1 data, explicitly blame (attitude) explicit blame (behavior) as much as 2 data. gb777gb777slot gacorgb777gb777GB777GB777